2019
DOI: 10.3390/atmos10080426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Aqua-MODIS C6 and C6.1 Aerosol Optical Depth Products in the Yellow River Basin, China

Abstract: In this study, Aqua-Moderate Resolution Imaging Spectroradiometer (MODIS) Collection (C6) and C6.1 Dark Target aerosol optical depth (AOD) retrievals at 3 km (DT3K) and 10 km (DT10K), Deep Blue AOD retrievals at 10 km (DB10K), and combined DT and DB (DTB) AOD retrievals at 10 km resolutions were validated from 2002 to 2014 against ground-based sunphotometer AOD measurements obtained from the Chinese aerosol remote sensing network (CARSNET). The CARSNET AOD data were obtained for sites at Mt. Waliguan (MW), Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 64 publications
(114 reference statements)
1
10
0
1
Order By: Relevance
“…This phenomenon is caused mainly by the fact that the MYD04 C6.1 DT3K images had higher resolutions. On the other hand, the reason could be that C6.1 DT10K has few retrievals for the water system over the YERB, as mentioned by (Zhang et al 2019b). Figure 4 shows the validation of the MYD04 C6.1 DB10K AOD and CALIPSO AOD over the YERB area.…”
Section: Comparison Of Aqua-modis C61 Aod With Calipso Aodmentioning
confidence: 99%
See 4 more Smart Citations
“…This phenomenon is caused mainly by the fact that the MYD04 C6.1 DT3K images had higher resolutions. On the other hand, the reason could be that C6.1 DT10K has few retrievals for the water system over the YERB, as mentioned by (Zhang et al 2019b). Figure 4 shows the validation of the MYD04 C6.1 DB10K AOD and CALIPSO AOD over the YERB area.…”
Section: Comparison Of Aqua-modis C61 Aod With Calipso Aodmentioning
confidence: 99%
“…Since MODIS aerosol products are updated frequently, many scholars have carried out a large number of verification studies of new MODIS AOD products by comparing them with AERONET or CARSNET ground-based remote sensing data (Bilal et al 2018;Che et al 2015;Dubovik et al 2012;He et al 2017;Shi et al 2019;Wang et al 2019). Zhang et al (2019b) evaluated the performance of MODIS Collection C6.1 (C6.1) AOD products over the Yellow River basin (YERB) by comparing the AOD data from ground-based CARSNET site and obtained good results (Zhang et al 2019b). The study suggested that no single satellite AOD product performed satisfactorily over YERB.…”
mentioning
confidence: 99%
See 3 more Smart Citations